Pregnancy outcomes in mixed connective tissue disease: a multicentre study. (11th May 2019) - Radin, Massimo; Schreiber, Karen; Cuadrado, Maria José; Cecchi, Irene; Andreoli, Laura; Franceschini, Franco; Caleiro, Teresa; Andrade, Danieli; Gibbone, Elena; Khamashta, Munther; Buyon, Jill; Izmirly, Peter; et al.
Abstract: Objectives: In this study we aimed to investigate foetal and maternal pregnancy outcomes from a large multicentre cohort of women diagnosed with MCTD and anti-U1RNP antibodies. Methods: This multicentre retrospective cohort study describes the outcomes of 203 pregnancies in 94 consecutive women ever pregnant who fulfilled the established criteria for MCTD with confirmed U1RNP positivity. Results: The foetal outcomes in 203 pregnancies were as follows: 146 (71.9%) live births, 38 (18.7%) miscarriages (first trimester pregnancy loss of <12 weeks gestation), 18 (8.9%) stillbirths (pregnancy loss after 20 weeks gestation) and 11 (5.4%) cases with intrauterine growth restriction. Maternal pregnancy outcomes were as follows: 8 (3.9%) developed pre-eclampsia, 2 (0.9%) developed eclampsia, 31 (15.3%) developed gestational hypertension and 3 (1.5%) developed gestational diabetes. Women with MCTD and aPL and pulmonary or muscular involvement had worse foetal outcomes compared with those without. Moreover, we report a case of complete congenital heart block (0.45%) and a case of cutaneous neonatal lupus, both born to a mother with positive isolated anti-U1RNP and negative anti-Ro/SSA antibodies. Conclusion: In our multicentre cohort, women with MCTD had a live birth rate of 72%. While the true frequency of heart block associated with anti-U1RNP remains to be determined, this study might raise the consideration of echocardiographic surveillance in this setting. Pregnancy counselling should be considered in women with MCTD.